Neonatal Outcome After Preeclampsia and HELLP Syndrome: A Population-Based Cohort Study in Germany - Bossung, Verena; Fortmann, Mats Ingmar; Fusch, Christoph; Rausch, Tanja; Herting, Egbert; Swoboda, Isabelle; Rody, Achim; Härtel, Christoph; Göpel, Wolfgang; Humberg, Alexander (Frontiers in Pediatrics, 2020)
Aim: To analyze short term outcomes of very low birth weight infants (VLBWI) born preterm after maternal preeclampsia and HELLP syndrome within the German Neonatal Network. Methods: The German Neonatal Network is a large population-based cohort study enrolling VLBWI since 2009. Two thousand six hundred and fifty two infants below 32 weeks of gestation born after maternal preeclampsia or HELLP syndrome and 13,383 infants born prematurely for other causes between 2009 and 2018 were included in our analysis. Descriptive statistics and multinomial regression models including preeclampsia and HELLP syndrome were performed for short-term outcome measures such as intracerebral hemorrhage, necrotizing enterocolitis requiring surgery, bronchopulmonary dysplasia, retinopathy of prematurity, periventricular leukomalacia, persistent ductus arteriosus requiring surgery, blood culture positive sepsis and death. Results: After adjustment for confounding variables, preterm birth due to preeclampsia or HELLP syndrome was associated with a reduced risk for intracerebral hemorrhage (OR 0.73, 95% CI 0.60–0.89), necrotizing enterocolitis requiring surgery (OR 0.35 95% CI 0.15–0.82), periventricular leukomalacia (OR 0.61 95% CI 0.40–0.92), and death (OR 0.72 95% CI 0.55–0.96) as compared to other causes of preterm birth. Conclusions: The indication for preterm birth has an impact on neonatal outcome in preterm infants born below 32 weeks. This notion should be included when counseling the families.